Larval occurrence, oviposition behavior and biting activity of potential mosquito vectors of dengue on Samui Island, Thailand - Usavadee Thavara (2018)
A 1995 outbreak of dengue haemorrhagic fever (DHF) occurred on Samui Island in Thailand with an incidence of almost 500 cases/100,000 population. To find and develop effective strategies to control this disease through cost-effective vector control programs, entomological studies were carried out on the island between 1996 and 1998. There were two species of DHF vectors, Aedes aegypti and Ae. albopictus prevailing on the island, and the population of Ae. aegypti remained relatively constant throughout the year while the abundance of Ae. albopictus increased substantially during the rainy season (May-December) and then declined drastically in the dry season (January-April). The ranges of the three Aedes larval indices, Breteau index (BI), house index (HI) and container index (CI) were 93-310, 43-89 and 16-50 respectively. The ceramic or earthen jars both inside and outside the dwellings and concrete water storage tanks (mostly in toilets and bathrooms) served as the main breeding places of Ae. aegypti whereas coconut husks and coconut floral spathes found outdoors were the major breeding sites of Ae. albopictus. The number of washing water jars, concrete tanks and natural sites infested with Aedes larvae increased significantly in rainy season, with 60% of ovitraps become positive for Ae. albopictus eggs with an average number of 26 eggs/trap in 3 days of setting. There was a complete lack of oviposition by Ae. aegypti in outdoor ovitraps (15m away from the houses). The indoor biting rate ranged from 1.5 to 8.1 mosquitoes/ man-hour, while the outdoor rate was between 5 and 78 mosquitoes/man-hour. Of the indoor biting mosquitoes, 75.4% were identified as Ae. aegypti and 99% of the outdoor ones were Ae. albopictus. The diel biting activity of Aedes during the period from 0800 h to 1700 h in the houses was higher in the morning than in the afternoon period, with a low prevalence between 1300 h and 1400 h.